ANAUSIS KOMPONEN KIMIA MINYAK TERPENTIN DARI CIANJUR DAN REKALONGAN TIMUR - Abdul Hakim Lukman; Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
77&e purpoae of the study is to identify chemical oomponents of turpentine oils from Ciaft.;ur, West Java, and Pekalongan flmlD', Central Java. The analysia was conducted using Gas Chromatography method, The relative retention time of . thfl standard solution. before the emergence of apinene peak was predetermined prior to the analyaisof the apine111 of the 1amplea.The peak areaof each chemical components was then calculated by normalization method .• • . 7'ae lta showed !hat there are res ctively, _ 12 and 7 compo.nent8.of turpe'!ti1!Bidenti.fied from samples.from CiatVuraruf Pekalongan TimlD'. The chemical components of turpentine 011 'from Cnrvur corm.fed of a and IJp1nene, camphene, 113carene, limonene, IJphellandrene,a and 'Yterpinene,p-cymene, terpinolene, cilryophyllene, and humulene.7Jaoae from Pekalongan Timur comprised a and fJpinene,camphene, 113carene, terpinene, limonene, and caryophyllene.'IJaeJ.pineneforms the mayor portion of turpentine oil, amounting to 72.9% from Cianjur and 71.3% from Pekalongan flmw.